Investigating the Role of English Language as International Medium for Learning Medical Sciences - Abdelrahman Elyass Mohamed Abdelmajd; Hassan Mahill Abdallah Hassan (Journal of English Language Teaching and Linguistics, 2017)
This paper aims to answer “To what extent English Language as International Medium can help for Learning Medical Sciences?" The researcher has adopted the quantitative method as well as the questionnaire as a tool for collecting data relevant to the study to bring to the light the importance of English Language as International Medium for Learning Medical Sciences. The sample of this study comprises (60) students. The marks obtained from the questionnaire were compared. From one hand, the results have revealed that the students encountered difficulties in   understanding the Medical Sciences. The result has shown that the questionnaire significance indicates that there is highly difference among students.  Therefore, this indicates that English Language as International Medium can play a great role for Learning Medical Sciences.